Efectos de varios tipos de sustratos en el desarrollo inicial del cultivo de Moringa (Moringa oleífera Lam) - Burgos Bajaña, Lizbeth Leonela (2019)
VIII. SUMMARY The present experimental research work was carried out in lands of the Technical University of Babahoyo, located 7.5 km from the Babahoyo - Montalvo highway; with UTM coordinates This X = 662937,2477 UTM; North Y = 201426,1986 and an altitude of 8 masl. The place presents a tropical climate, with an average annual temperature of 24.7 ºC, average annual precipitation of 2791.4 mm / year, relative humidity of 83.93 % and 3.5 hours of average heliophany per day. Selected seed of the Moringa oleifera Lam variety was used, coming from the local market. The treatments established were clay loam 50 %; Tamo de Madera (Balsa) 25 % and Organic matter (Humus) 25%; Sandy loam 50%; Tamo de Madera (Balsa) 25 % and Organic matter (Humus) 25 %; Sand 50 % and Organic matter (Humus) 50 %; Loamy silt 50 %, Wood Tamo (Balsa) 25 %, Sand 15 % and Organic matter (Humus) 10 % and clay loam without any mixture. In the present work, the experimental design of Complete Blocks at Random was used with 5 treatments and 4 repetitions. We proceeded to draw the experimental units for the allocation of each treatment. The statistical significance of the treatments was determined, performing the variance analysis, performing the Duncan multiple range test at 95 % probability. For the development of the experimental test were carried out the agricultural practices and work that required the cultivation for its development as land preparation, planting, weed control, pest control, fertilization and irrigation. To estimate the effects of the treatments, data were taken on plant height, number of leaves, stem diameter, leaf length and width, leafiness and root development. For the results obtained, it was determined that the highest plant height, number of leaves, length and width of the leaf from 14 to 115 days was obtained with the use of the base of loamy clay soil 50% with 25 % of wood chaff (raft) and 25 % of organic matter (humus) and in relation to the diameter of the stem, leafiness and root development was higher average using clayey loam soil 50% with 25 % of wood chaff (balsa) and 25 % of matter organic (humus).